Analysis and simulation of even-level quasi-Z-source inverter - Niltala Sai shanmukha Akshath; Avugaddi Naresh; Matcha Nikesh kumar; Mayur Barman; Durgesh Nandan; Tirupathi Abhilash (International Journal of Electrical and Computer Engineering (IJECE), 2022)
This research proposes a seven-level inverter with quasi-Z-source boost converters. The proposed topology employs a packed U-cell asymmetrical type multilevel inverter along with front-end quasi-Z-source networks. The quasi networks provide high gain compared to a conventional boost converter. This topology is the most suitable for photovoltaic multi-string applications. The proposed topology has the potential to supply both the alternating current (AC) and direct current (DC) type load. The inverter structure has a lower number of active switches which helps in the reduction of losses and improvement in efficiency. In this paper, the operation principle of a quasi-network and inverter circuit are explained in detail. In addition, the simulation results for various modulation indices are presented. In the MATLAB/Simulink environment, the architecture is proposed by using gated sinusoidal “Pulse width modulation”.